A new steganography technique using Knight's Tour algorithm, Affine Cipher and Huffman Coding - Alla Talib Mohsin, 1986-; Ghazali Sulong; Fakulti Komputeran (2013)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2013